A combinatorial approach for transmission expansion & reactive power planning - Rahmani, M. [UNESP]; Rashidinejad, M.; Carreno, E. M.; Romero, R. A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
A metaheuristic technique for solving the short-term transmission network expansion and reactive power planning problems, at the same time, in regulated power systems using the AC model is presented. The problem is solved using a real genetic algorithm (RGA). For each topology proposed by RGA an indicator is employed to identify the weak buses for new reactive power sources allocation. The fitness function is calculated using the cost of each configuration as well as constraints deviation of an AC optimal power flow (OPF) in which the minimum reactive generation of new reactive sources and the active power losses are objectives. With allocation of reactive power sources at load buses, the circuit capacity increases and the cost of installation could be decreased. The method is tested in a well known test system, presenting good results when compared with other approaches. © 2011 IEEE.
Keywords: L indicator; reactive power planning; reactive sources; real genetic algorithm; transmission expansion planning; weak buses; Buses; Electric power transmission; Expansion; Genetic algorithms; Reactive power